2017
DOI: 10.1590/1678-4324-2017160466
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Genetic Relationship in the Tree of Life of Some Quail Through Molecular Markers Analyses

Abstract: Quail is an important and interesting group of galliform birds. The Common quail (Coturnix coturnix); the Japanese quail (Coturnix japonica); the Panda quail (Coturnix japonica); the Dotted white quail (Coturnix japonica) and the Bobwhite quail (Colinus virginianus) were used in this study. PCR-RFLP and SDS-proteins were performed to reveal the genetic characterization and genetic relationship of the studied quails. Analysis of fragments generated by digestion of PCR product with restriction enzyme NlaIII reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…and TLX loci to study recombination frequencies in the Japanese quails populations out of the eight loci studied (SEMA3E, IFR1, HAL, LOC396025, UGP2, LOC396192, TLX and BMP5), polymorphism was detected in the SEMA3E and TLX loci; five of their loci were regarded as monomorphic and one locus (HAL) wasn't amplifiable by PCR. Deef et al (10) indicated that the PCR-RFLP was performed in terms of revealing the genetic characterization and also genetic relationship of the five species of quails. The Common quails are found to be Coturnix coturnix, bobwhite quail Colinus virginianus, and three quails belong to Coturnix japonica including panda quail, Japanese quail, dotted white quail.…”
Section: Molecular Characterization Of Local Quailmentioning
confidence: 99%
“…and TLX loci to study recombination frequencies in the Japanese quails populations out of the eight loci studied (SEMA3E, IFR1, HAL, LOC396025, UGP2, LOC396192, TLX and BMP5), polymorphism was detected in the SEMA3E and TLX loci; five of their loci were regarded as monomorphic and one locus (HAL) wasn't amplifiable by PCR. Deef et al (10) indicated that the PCR-RFLP was performed in terms of revealing the genetic characterization and also genetic relationship of the five species of quails. The Common quails are found to be Coturnix coturnix, bobwhite quail Colinus virginianus, and three quails belong to Coturnix japonica including panda quail, Japanese quail, dotted white quail.…”
Section: Molecular Characterization Of Local Quailmentioning
confidence: 99%